Four new species of Halozercon (Acari: Mesostigmata: Zerconidae) from South Siberia Mountains (Russia) with a key to all known species - Marchenko, Irina I. (Zootaxa, 2021)
Four new species of zerconid mites of the genus Halozercon are described and illustrated based on material collected from litter and soil in Altai and Tuva mountains, South Siberia, Russia—H. alataus sp. n., H. gryphus sp. n., H. kumir sp. n. and H. aesopi sp. n. Morphological characters for the new Halozercon species are given. A key for all known species of Halozercon is attached.